Predictors of Emergency Department and Inpatient Readmissions among Homeless Adolescents and Young Adults - Mackelprang, Jessica L. (Med Care, 2015)
BACKGROUND: Individuals under age 25 years are estimated to comprise one-third of the homeless population nationally. Understanding reasons homeless youth utilize hospitals is important for optimizing disposition planning. OBJECTIVES: (1) Report prevalence of emergency department (ED) and inpatient admissions among homeless and unstably housed youth; (2) describe demographic characteristics of those youth who seek hospital care; (3) describe their patterns of injury, illness, psychiatric, and substance use conditions; and (4) identify demographic and diagnostic predictors of ED visit or hospital readmission. METHODS: Retrospective cohort study of 15-25 year-olds (N=402) who were admitted to the ED or inpatient floors of two urban teaching hospitals in King County, Washington between July 1, 2009 and June 30, 2012 and whose address was “homeless” or “none” or a homeless shelter or service agency (i.e., homeless or unstably housed), during any recorded encounter between July 1, 2009 and June 30, 2012. RESULTS: 1151 ED visits and 227 inpatient admissions were documented. Fifty percent of patients had an ED visit or hospital readmission within one year, with 43.1% receiving care within 30 days of discharge. Cox regression showed females with an injury diagnosis (hazard ratio [HR]=1.74, 95% confidence interval [CI]=1.06, 2.85) and males with an acute medical condition (HR=1.59, 95% CI=1.09, 2.32) at index visit were more likely to have an ED visit or hospital readmission during the following year, as were patients who provided a private address at their index visit. CONCLUSIONS: Homeless young people who seek hospital care demonstrate a high rate of ED visits and hospital readmissions, with unique predictors of utilization associated with sex and housing status. Additional research is necessary to determine how best to transition these young people from hospital- to community-based care.